ANALYSIS OF POST-PANDEMI ETHICS PRACTICES FOR FUTURE ACCOUNTANTS - Pratama, Bagas Brian (UNKLAB Business School, 2024)
This study analyzes the threats to professional accountants' ethical practice in the new normal era after the Covid-19 pandemic. The method uses a literature study with four stages of analysis. First, is data collection using a literature study. Articles used as references use databases from ScienceDirect, Scopus, EBSCO, SINTA, and ProQuest which were published in 2020 to 2022 with the keywords